SHORT-TERM OUTCOME OF LAPAROTOMIC MYOMECTOMY WITH TRANSIENT UTERINE VESSELS OCCLUSION IN INFERTILE PATIENT - Najmutdinova, D.K.; Saparov, A.B. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To evaluate the effectiveness of myomectomy with intraoperative temporary ligation of uterine vessels in patients with infertility. Material and methods: the study included data from 61 patients suffering from a combination of infertility and uterine fibroids, who required surgical treatment. All patients were operated on at the Department of Gynecology No. 1 of the State Administration of the Republican Specialized Scientific Center of Obstetrics and Gynecology in 2015-2018. The data of 43 retrospective analyzed patients who underwent myomectomy underwent a permanent uterus ligation procedure and 7 patients who underwent uterus ligation during myomectomy were not analyzed at all. The prospective part of the study included data from 11 patients who underwent a temporary ligation of the uterine vessels when performing myomectomy. Results: temporary ligation of uterine vessels during myomectomy has a beneficial effect on short-term surgical outcomes, such as intraoperative blood loss, hemoglobin blood in the blood, periods of recovery of bowel function, the need for analgesics, as well as discharge periods after surgery. The positive effect in patients with temporary ligation of the uterine vessels is manifested to a greater extent than in patients with permanent. Conclusions: for a comprehensive study of the place of temporary ligation of the uterine vessels when performing myomectomy, women with infertility should conduct further research to assess long-term (reproductive and ovarian) outcomes.